Controlling Intramolecular Förster Resonance Energy Transfer and Singlet Fission in a Subporphyrazine–Pentacene Conjugate by Solvent Polarity. Issue 3 (18th November 2020) - Guzmán, David; Papadopoulos, Ilias; Lavarda, Giulia; Rami, Parisa R.; Tykwinski, Rik R.; Rodríguez‐Morgade, M. Salomé; Guldi, Dirk M.; Torres, Tomás
Abstract: Due its complementary absorptions in the range of 450 and 600 nm, an energy‐donating hexaaryl‐subporphyrazine has been linked to a pentacene dimer, which acts primarily as an energy acceptor and secondarily as a singlet fission enabler. In the corresponding conjugate, efficient intramolecular Förster resonance energy transfer (i‐FRET) is the modus operandi to transfer energy from the subporphyrazine to the pentacene dimer. Upon energy transfer, the pentacene dimer undergoes intramolecular singlet fission (i‐SF), that is, converting the singlet excited state, via an intermediate state, into a pair of correlated triplet excited states. Solvatochromic fluorescence of the subporphyrazine is a key feature of this system and features a red‐shift as large as 20 nm in polar media. Solvent is thus used to modulate spectral overlap between the fluorescence of subporphyrazine and absorption of the pentacene dimer, which controls the Förster rate constant, on one hand, and the triplet quantum yield, on the other hand. The optimum spectral overlap is realized in xylene, leading to Förster rate constant of 3.52×10 11 s −1 and a triplet quantum yield of 171 % ±10 %. In short, the solvent polarity dependence, which is a unique feature of subporphyrazines, is decisive in terms of adjusting spectral overlap, ensuring a sizable Förster rate constant, and maximizing triplet quantum yields. Uniquely, this optimization can be achieved without a need for synthetic modification of the subporphyrazine donor. Abstract : The solvatochromic fluorescence properties of a subporphyrazine are used to control the rate of intramolecular Förster resonance energy transfer (i‐FRET) in a subporphyrazine–pentacene conjugate (SubPzPnc2 ) that undergoes intramolecular singlet fission (i‐SF). A simple selection of solvent serves to optimize the triplet quantum yield by enhancing the spectral overlap between the fluorescence of the SubPz and the absorption of the Pnc dimer.